Small houses for Filipino newlyweds - Balajadia, Ma. Cristina Joy M.; Mayo, Adelaida Villaraza (1998.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Dwellings; Newlyweds